2016
DOI: 10.17705/1jais.00428
|View full text |Cite
|
Sign up to set email alerts
|

Unified Theory of Acceptance and Use of Technology: A Synthesis and the Road Ahead

Abstract: The unified theory of acceptance and use of technology (UTAUT) is a little over a decade old and has been used extensively in information systems (IS) and other fields, as the large number of citations to the original paper that introduced the theory evidences. In this paper, we review and synthesize the IS literature on UTAUT from September 2003 until December 2014, perform a theoretical analysis of UTAUT and its extensions, and chart an agenda for research going forward. Based on Weber's (2012) framework of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,393
8
65

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,446 publications
(1,512 citation statements)
references
References 63 publications
(230 reference statements)
46
1,393
8
65
Order By: Relevance
“…The intent was to further the discussion in HRM literature as to how ESM impacts employees in Nigeria. We found evidence that performance expectancy positively impacted ESM use, thus complementing numerous other western studies findings (Venkatesh et al 2016). The logic is that if one expects ESM to improve their performance then it would lead to use.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The intent was to further the discussion in HRM literature as to how ESM impacts employees in Nigeria. We found evidence that performance expectancy positively impacted ESM use, thus complementing numerous other western studies findings (Venkatesh et al 2016). The logic is that if one expects ESM to improve their performance then it would lead to use.…”
Section: Discussionsupporting
confidence: 89%
“…El Ouirdi et al (2016 found that being a younger male instead of a female was significantly related to effort expectancy and behavior intention. This was contrary to many other studies which found being a female would influence use (Venkatesh et al 2016 (Venkatesh et al 2003;Venkatesh et al 2012). Morris and Venkatesh (2000) found that an age difference exists when it comes to technological adoption.…”
Section: Unified Theory Of Acceptance and Use Of Technologycontrasting
confidence: 80%
See 1 more Smart Citation
“…Quite a number of scholars have used UTAUT to provide empirical insights into the acceptance of different technologies by different individuals in a variety of settings (Venkatesh, Thong, & Xu, 2016). However, the studies that relate to the main objective of this study will now be reviewed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Let us consider a well-known example in IT use-namely, ease of use (Venkatesh, Thong, & Xu, 2016). For example, ease of use could be further associated with concrete system features and then examined to determine to what extent improving these concrete system features actually improves IT use.…”
Section: Applicability Of Our Ideas Beyond Is Security and Further Dementioning
confidence: 99%